Avaliação da acessibilidade de pessoas com deficiência física no transporte coletivo urbano - Rabelo, Gilmar Borges (2008)
The issue accessibility to the disable people has been reason of great debate in some segments of the society, mainly to the economic sector. In the specific case of transportation, either urban or interurban, there are adequacies necessary to make it accessible, mainly to the disable people. The general objective of this work was to analyze the accessibility of the people with physical disability in the urban public transportation regarding the fulfillment of the laws and technical regulations related to the subject. The specific objective was to evaluate the accessibility of the public transportation service offered by the city of Uberlândia, Brazil using the results from a survey with disable users. In addition, physical spaces were observed, beginning with the sidewalks, which are used for the trips by foot, as well as equipments and vehicles used in the deployment of the public transportation service. In the public transportation system of the city of Uberlândia, Brazil it was verified what was already deployed, how was it working and if the service is in according to the existing laws. In the end, some directions were presented for orientation of the administrators and operators in the deployment and adjustment of the service. It is expected that this work provides to the readers a better understanding of the necessities of a public transportation that can be used by any person, despite of his/her physical condition, making possible the creation of a critical visualization by public administrators and operators in the execution of projects for the deployment and adaptation of urban public transportation systems with autonomy and safety to passengers.